High b-Value Diffusion MRI to Differentiate Recurrent Tumors from Posttreatment Changes in Head and Neck Squamous Cell Carcinoma: A Single Center Prospective Study - Acampora, Angela (Biomed Res Int, 2016)
Recently DW-MR Imaging has shown promising results in distinguishing between recurrent tumors and posttreatment changes in Head and Neck Squamous Cell Carcinoma (HNSSC). Aim of this study was to evaluate the diagnostic performances of DWI at high b-value (b = 2000 s/mm(2)) compared to standard b-value (b = 1000 s/mm(2)) and ADC(ratio) values (ADC(ratio) = ADC(2000)/ADC(1000) × 100) to differentiate recurrent tumors from posttreatment changes after treatment of HSNCC. 20 patients (16 M, 4 F) underwent MR Imaging between 2 and 16 months (mean 7) after treatment. Besides morphological sequences, we performed single-shot echo-planar DWI at b = 1000 s/mm(2) and b = 2000 s/mm(2), and corresponding ADC maps were generated (ADC(1000) and ADC(2000), resp.). By considering contrast-enhanced T1-weighted images as references, ROIs were drawn in order to evaluate mean ADC(1000), ADC(2000), and ADC(ratio). The mean ADC(1000) and ADC(2000) in recurrent tumors were significantly lower than those in posttreatment changes (P = 0.001 and P = 0.016, resp.). Moreover, the mean ADC(ratio) between the two groups showed a statistically significant difference (P = 0.002). Sensitivity, specificity, and accuracy of ADC(ratio) were 82.0%, 100%, and 90%, respectively, by considering an optimal cutoff value of 65.5%. ADC(ratio) is a promising value to differentiate between recurrent tumors and posttreatment changes in HNSCC and may be more useful than ADC(1000) and ADC(2000).